Peaceful Fiqh; Jürgen Habermas’s Hermeneutical Studies in the Verses of Jihad - Kurnia Muhajarah; Alifa Nur Fitri (The Institute of Research and Service Community IPMAFA Pati, 2022)
The most crucial problem in analyzing problematic violence in Islam is when relating it with text religion. Problematic violence will appear more paradoxical and crucial when trying to legitimize al-Qur'an. When violence and terrorism get legitimacy from al-Qur'an, it will lead to a very risky conclusion; namely, Islam supports violence and terrorism. This is where the hermeneutics of Jurgen Habermas tries to review the problem of interpretation of these verses, especially concerning the theory of communication actions which will be used as an analytical knife in this study. The problem formulation is; how to read verse jihad without using instrumental interpretation and more developed paradigm communicative hermeneutics. The result of this research is that Jurgen Habermas's view will presuppose the formation of an intersubjective relationship in social society. The act of communication aims to reach an understanding between individuals. In relation to religious tolerance, the expected communication is a dialogue in reaching agreement on claims of accuracy in the underlying values ​​of each religion on how to build agreement on each religion and that peace is beautiful and violence is terrible. This claim necessitates an interactive dialogue that explores holistic religious values but avoids discussing truth claims considered non-negotiable religious doctrines. When it is applied in the interpretation of the jihad verse, the conclusion that we hope for is the jihad verse cannot abolish the universal value contained in the peace verse.